- 7

- 0

## Main Question or Discussion Point

Can you please tell me how theta1 was obtained from this system:

Px=C1(a2*C2+d4*S23)-d2*S1

Py=S1(a2*C2+d4*S23)+d2*C1

theta1=atan((Py*sqrt(Px^2+Py^2-d2^2)-d2*Px)/(Px*sqrt(Px^2+Py^2-d2^2)+d2*Py))

theta1=atan((-Py*sqrt(Px^2+Py^2-d2^2)-d2*Px)/(-Px*sqrt(Px^2+Py^2-d2^2)+d2*Py))

Px=C1(a2*C2+d4*S23)-d2*S1

Py=S1(a2*C2+d4*S23)+d2*C1

theta1=atan((Py*sqrt(Px^2+Py^2-d2^2)-d2*Px)/(Px*sqrt(Px^2+Py^2-d2^2)+d2*Py))

theta1=atan((-Py*sqrt(Px^2+Py^2-d2^2)-d2*Px)/(-Px*sqrt(Px^2+Py^2-d2^2)+d2*Py))